Consumer behaviour determinants: evidence from MBA students - Osuagwu, Linus (Journal of Management and Business Education, 2022)
The Masters in Business Administration (MBA) programme is a global educational qualification with different forms of values for individuals and organisations and varying degrees of attractions from persons and companies in developed and developing countries. Therefore, many factors motivate individuals and organizations to choose MBA programmes. This research utilised a survey research method, with a research instrument developed from relevant extant literature, to isolate the major factors determining students’ choice behaviour towards MBA programmes in the Nigerian university system. The research reports that the major factors determining students’ choice behavior towards MBA programs include quality-related, information-related, and convenience-related factors. The limitations associated with the research relate to its cross-sectional nature, in addition to the usual limitations associated with the survey research method used in this research. In addition, the combination of MBA students from both private and government-owned universities is likely to pose some limitations. Also, focusing on students from only one country (Nigeria) presents external validity limitations. The research has practical implications for administrators and regulators of business programs in the Nigerian university system, in addition to organizational decision-makers interested in sponsoring their relevant staff for MBA programs in the Nigerian university system. The research has social implications about the different cohorts of students interested in MBA programmes in the Nigerian university system.